The dynamic of deforestation and economic growth in the Brazilian Amazon - Andersen, L.E.; Granger, C.W.J.; Reis, E.J.; Weinhold, D.; Wunder, Sven (Cambridge University Press, 2002)
This book presents an empirical analysis of the development processes and the economic of Brazilian Amazon deforestation using a large data set of ecological and economic variables. It presents summary statistics and analyse trends for a number of important variables as well as developing econometric models to analise policies and compare outcomes under different scenarios. The analyses based on municipality level data for the entire region at several points in time between 1970 and 1996. Throughout the book the models and analyses pay due respect to the dramatic spatial differences in vegetation, soil, rainfall, market access, population density, and many other important factors. By observing the dynamics of land-use change over such a long period this book provides quantitative estimates of the long-term economic costs and benefits of both land clearing and government policies such as road building.